Injuries at Johannesburg high school rugby festivals - Constantinou, Demitri (My University, 2014)
Aim. The aim of the study was to analyse the prevalence and type of injuries over two years of a Johannesburg High School rugby festival by assessing the injuries (number, anatomical sites, types and severity), to compare the injuries between the two years and to compare the injuries between the three days of the festival. Methods. The study design was a retrospective, descriptive and observational study. The study population was the participating rugby players at the two rugby festivals in 2010 and 2011. Medical records of rugby related injuries in schoolboy participants were used for capturing injury data. Results. A total of 626 players participated (322 and 304 in 2010 and 2011 respectively) of which there were a total of 100 injury data sets analysed. The injury rate per player in year one was 16.8%, and 15.2% in year two. There was no statistical difference (P = 0.6526) in the injury numbers between the two years. The injury profiles between the respective days between the two years were not statistically different. Most injuries were to the head/face, with the majority being concussion related. The next commonest injuries were to the neck area. Most injured players had not had previous similar injuries. Tackles were the commonest mechanism of injuries. Twenty four percent of injuries were deemed severe enough to stop the players from continuing play. Few required referral for investigations or specialist physician care and most were managed with simple first aid at the primary care level. Conclusion. The nature and mechanisms were in keeping with numerous local and international studies of schoolboy rugby players, but with a lower injury frequency. Providing medical services at rugby events such as these festivals is a requirement and adequate standardised record keeping is recommended to increase knowledge and monitor trends as the dynamic nature of the game of schoolboy rugby continues to develop and change.
Thesis (M.Sc.(Emergency Medicine))--University of the Witwatersrand, Faculty of Health Sciences, 2014.
Keywords: Sports Medicine; Football--injuries